KEMAMPUAN KERJA TENAGA MEDIS DI PUSAT KESEHATAN MASYARAKAT TARIPA KECAMATAN PAMONA TIMUR KABUPATEN POSO - BANDO, PUTRI AGRIANE; OGOTAN, MARTHA; PALAR, NOVIE ANDERS (Sam Ratulangi University, 2018)
This research was conducted for the purpose of explaining the ability medics working in community healthcentres Taripa Subdistrict Pamona language East of Poso in the development of the science of publicadministration . Basic problems seen in Clinics is implementing health technical unit under the supervision ofhealth services District/City that still confronted on the issue the ability of medical personnel. This researchwith qualitative design, data were collected by means of interviews, observation and study of documentation.The data collected is analyzed through categorization and data reduction, data grouped subsequently draftedin the form of narratives, so data-shaped series of meaningful information in accordance with the researchissues. m elakukan on data interpretations and conclusions based on the order of narration have beencompiled on the third stage, so that it can give an answer to the problem of research. The study found that theability of medical personnel working in community health centres Taripa Subdistrict Pamona language Eastof Poso which is examined from intellectual ability, interpersonal skills, adaptability and results orientationcapability has not been done properly. Suggested improvements To make improvements in terms of staffingstatus of medical personnel, provide incentives that match workload to medical personnel, improve theplanning pattern for this to happen in a way do the preparation of plans and service needs sesai with konsisiwork unit and includes medical personnel in health pelatuhan handler activities according to the needs in thehealth service in the ability of medical personnel working in the Centre Public Health.Keywords: Ability, Work, Medical Personnel.